Strength in numbers : population, reproduction, and power in eighteenth-century France - Blum, Carol, 1934- (Johns Hopkins University Press, 2002)
"In the eighteenth century France became convinced it was losing population. While not technically true (France was merely failing to gain population as rapidly as Great Britain and the German states), the public's belief in a national fertility crisis had far-reaching consequences. In Strength in Numbers: Population, Reproduction, and Power in Eighteenth-Century France, Carol Blum shows how intellectuals used "natalism" as a means of criticizing the monarchy and the Catholic Church in their pursuit of social change."--Jacket